Analisis Aktivitas Antibakteri Ekstrak Etil Asetat Tanaman Sirih Cina (Peperomia pellucida L.) pada Bakteri Shigella Dysenterie - A. Nurul Fitriandini Ekaputri; Indah Woro Utami; Eka Kumala Retno (An-Najat, 2025)
Dysentery is a gastrointestinal infection characterized by bloody or mucoid diarrhea, abdominal pain, and tenesmus. One of its main causative agents is Shigella dysenteriae , a Gram-negative bacterium capable of causing epidemics and showing resistance to various antibiotics. Therefore, alternative treatments are needed, one of which is the use of traditional medicinal plants such as Peperomia pellucida L. (“sirih cina”). This study aimed to determine the ability of the ethyl acetate extract of Peperomia pellucida L to inhibit the growth of Shigella dysenteriae , and to identify the most effective concentration in exhibiting antibacterial activity. The research was conducted experimentally in the laboratory, involving simplisia preparation, maceration extraction with ethyl acetate, phytochemical screening, and antibacterial testing using the agar well diffusion method. Three extract concentrations were tested (20%, 25%, and 30%), with ciprofloxacin (5 µg) as the positive control and 5% DMSO as the negative control. Phytochemical screening revealed the presence of flavonoids, tannins, and terpenoids, while alkaloids, steroids, and saponins were not detected. Antibacterial assays showed that all extract concentrations inhibited the growth of S. dysenteriae with inhibition zones >20 mm (classified as very strong). The highest activity was observed at 30% concentration with an average inhibition zone of ±22.6 mm, approaching the effectiveness of ciprofloxacin. This study demonstrates that the ethyl acetate extract of P. pellucida possesses strong antibacterial activity and has potential as an alternative or combination therapy to reduce antibiotic resistance.